2016
DOI: 10.1021/acs.jmedchem.6b00967
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Selective Inhibitors Targeting Acetylcholinesterase 1 from Disease-Transmitting Mosquitoes

Abstract: Vector control of disease-transmitting mosquitoes is increasingly important due to the re-emergence and spread of infections such as malaria and dengue. We have conducted a high throughput screen (HTS) of 17,500 compounds for inhibition of the essential AChE1 enzymes from the mosquitoes Anopheles gambiae and Aedes aegypti. In a differential HTS analysis including the human AChE, several structurally diverse, potent, and selective noncovalent AChE1 inhibitors were discovered. For example, a phenoxyacetamide-bas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
25
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(27 citation statements)
references
References 75 publications
1
25
1
Order By: Relevance
“…In addition, 13 and analogs were demonstrated to be toxic to susceptible adult An. gambi ae [16, 17]. However, inhibitory potency of 13 against G119S Ag AChE was poor [17].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, 13 and analogs were demonstrated to be toxic to susceptible adult An. gambi ae [16, 17]. However, inhibitory potency of 13 against G119S Ag AChE was poor [17].…”
Section: Introductionmentioning
confidence: 99%
“…We have previously reported the in vitro screening campaigns of a chemically diverse library consisting of 17,500 drug-like compounds. The screens were performed using AChEs derived from Homo sapiens ( h AChE), Anopheles gambiae ( Ag AChE), and Aedis aegypti ( Aa AChE), and collectively led to the discovery of 425 unique hits that significantly reduced the enzymatic activity at a concentration of 50 µM [ 10 , 11 ]. Subsequent hit confirmation resulted in the determination of the half maximal inhibitory concentration values (IC 50 ) and Hill coefficients ( n H ) for 106 compounds.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have identified inhibitors that have greater selectivity for AgAChE than hAChE. An example of this was reported in a study in which differential high throughput screening (HTS) of several compounds for selective inhibition of AgAChE was carried out [47]. One of the selective inhibitors identified in their study was a phenoxyacetamide-based inhibitor that was 100-times more selective for AgAChE than for hAChE.…”
Section: Metabolic Proteins As Insecticide Targetsmentioning
confidence: 99%